Structural and genetic characterisation of variant glycoforms of Haemophilus influenzae lipopolysaccharide; implications for virulence - Schweda, E; Hood, D; Månsson, M; Martin, A; Richards, J; Richard Moxon, E (2010)
Haemophilus influenzae (Hi) type b transformants RM135 and RM133 were previously found to differ in virulence and capsule content [Zwahlen et a!., Microb Pathog 1986; 1: 465-73]. The more virulent strain RM135 produced less capsule than RM133, but was indicated to differ in its lipopolysaccharide (LPS). We have now performed detailed analyses of the respective LPSs and correlate structure, genetics and the original virulence observation. We found that RM133 expressed identical major LPS structures as the parent strain Rd whereas strain RM135 expressed shorter glycoforms. The genetic basis for this difference was found to be the expression of the phase-variable gene lie 2A, which could be shown to be compromised in RM135. The glycosyltransferase Lic2A is involved in the expression of a digalactoside (α-D-Galp-(1→4)-β-D-Galp(l→) and plays a role in chain elongation from the inner-core region of Hi LPS. One consequence of altered oligosaccharide extension, possibly contributing to the heightened virulence of RM135, was the sialylation of the LPSs. RM135 expressed W-acetylneuraminic acid whereas strain RM133 did not. Sialylation of LPS has been shown to be important for resistance of Hi to the killing effect of normal human serum. We thus propose that lie 2A expression can modulate virulence and that the effect of changes in LPS can outweigh that of capsule copy number. © 2010 Academic Journals Inc.